A matter between two extremes: A Study in Rational Analysis - Ayad Naeem Majeed ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
Since the mid-first century AH, theological debates have revolved around the issue of predestination and free will, specifically whether humans are free or compelled in their actions. Some Quranic verses assert that the sole agent is God, and that human actions are predetermined, while others emphasize human free will and responsibility for one's actions. Furthermore, the question of how to relate human agency to God's agency has been a perplexing one for human thought, particularly for scholars of Islamic schools of thought.The most important opinions in this field are divided  into three categories: the doctrine of predestination, held by the Ash'arites to defend the Oneness of God's actions, which led to neglecting divine justice; the doctrine of free will, chosen by the Mu'tazilites to defend divine justice, which also led to neglecting the Oneness of God's actions; and the Imamiyyah, who proposed the theory of "the middle ground" (al-amr bayna al-amrayn), which negates both predestination and free will, affirming the truth between them without compromising the fundamental principles of the Oneness of God's actions and divine justice. Based on their established principles, the Imamiyyah addressed the issue of free will in light of divine agency, aiming to reconcile the general concepts of divine decree, predestination, and power with human choice, since human actions, by virtue of their voluntary nature, are contingent upon God's power and will.In this study, we will analyze and critique these opinions to arrive at a preferred view, one that affirms that the manifestation of God's agency in the phenomena of creation is analogous to the agency of the soul in its facultiesDOI: https://doi.org/10.54633/2333-024-056-012